2015
DOI: 10.1186/s12931-015-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of pulmonary microvascular endothelial cell apoptosis in murine sepsis-induced lung injury in vivo

Abstract: BackgroundSepsis remains a common and serious condition with significant morbidity and mortality due to multiple organ dysfunction, especially acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Sepsis-induced ALI is characterized by injury and dysfunction of the pulmonary microvasculature and pulmonary microvascular endothelial cells (PMVEC), resulting in enhanced pulmonary microvascular sequestration and pulmonary infiltration of polymorphonuclear leukocytes (PMN) as well as disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 97 publications
4
126
0
1
Order By: Relevance
“…Recently, it was confirmed that apoptosis-mediated death of PMECs contributed to pulmonary microvascular barrier dysfunction in murine models of sepsis-induced ALI [25]. In the present study, we showed that fasudil protected pulmonary endothelial cells against LPS-induced apoptosis both in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, it was confirmed that apoptosis-mediated death of PMECs contributed to pulmonary microvascular barrier dysfunction in murine models of sepsis-induced ALI [25]. In the present study, we showed that fasudil protected pulmonary endothelial cells against LPS-induced apoptosis both in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 76%
“…EC death plays a significant role in pulmonary microvascular dysfunction associated with ALI following sepsis 9 . Lung ILC2 have been suggested to play a role in restoring airway integrity and lung tissue homeostasis 17 .…”
Section: Resultsmentioning
confidence: 99%
“…EC death triggered by lipopolysaccharide (LPS) and tumor necrosis factor α (TNFα) has been determined in septic mice 9,10 . Studies have shown that LPS through activating caspase-1 induces EC pyroptosis 11 , a caspase-1-dependent pro-inflammatory cell death type 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the production of proinflammatory cytokines in the kidney enhances inflammation and plays a critical role in the pathogenesis of renal injury [8]. In addition, sepsis is associated with evidence of apoptosis as reflected by increased caspase activation and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick-end labeling (TUNEL) [9]. Furthermore, sepsis leads to the production of ROS [10], which contributes to organ injury.…”
Section: Introductionmentioning
confidence: 99%